1975
DOI: 10.1192/bjp.126.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Is Unilateral ECT Less Effective Than Bilateral ECT?

Abstract: There is a general agreement about the less disruptive effect on memory and the shorter post-treatment confusion after unilateral electroconvulsive therapy (UNI-ECT) as compared with the traditional bifrontotemporal ECT (BI-ECT). However, there are divergent opinions about its therapeutic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…1,[7][8][9] When efficacy differences have been found, they consistently favored BL ECT. [10][11][12] Most patients in the United States receive BL treatment. Farah and McCall 13 conducted a survey of US ECT practitioners and found that 52% initiated ECT with the BL placement.…”
Section: Discussionmentioning
confidence: 99%
“…1,[7][8][9] When efficacy differences have been found, they consistently favored BL ECT. [10][11][12] Most patients in the United States receive BL treatment. Farah and McCall 13 conducted a survey of US ECT practitioners and found that 52% initiated ECT with the BL placement.…”
Section: Discussionmentioning
confidence: 99%
“…Ottosson (14) has concluded that the antidepressant effect is seizure-related and has a different neural substrate from the associated memory disturbance, and d'Elia (6) and Sand-Stromgren (15) have confirmed that unilateral non-dominant ECT has the same antidepressant effect as bilateral ECT; Doongaji et al . (7) state that both forms of treatment are equally effective in schizophrenia.…”
mentioning
confidence: 92%
“…Barely suprathreshold stimulation, brief or ultrabrief pulses, anticonvulsant drugs, and too deep a narcosis may interact in an unfortunate way to prevent the spread of the seizure from a unilateral focus. Submaximal seizures occur more often with unilateral than with bitemporal stimulation (46) and are the probable cause of lower efficiency of unilateral ECT (47,48).…”
Section: Electrode Placementmentioning
confidence: 99%